Role of socio-economic research in developing, delivering and scaling new crop varieties: the case of staple crop biofortification - Birol, Ekin; Bouis, Howarth E. (Frontiers in Plant Science, 2023)
The CGIAR biofortification program, HarvestPlus, was founded with the aim of improving the quality of diets through micronutrient-dense varieties of staple food crops. Implemented in four phases – discovery, development, delivery and scaling – the program was designed to be interdisciplinary, with plant breeding R&D supported by nutrition and socio-economic research. This paper explains the need, use and usefulness of socio-economic research in each phase of the program. Ex ante and ex post benefit-cost analyses facilitated fundraising for initial biofortification R&D and implementation in each subsequent phase, as well as encouraged other public, private, and civil society and non-governmental organizations to take on and mainstream biofortification in their crop R&D, policies, and programs. Socio-economics research helped guide plant breeding by identifying priority micronutrient- crop- geography combinations for maximum impact. Health impacts of biofortification could be projected both by using empirical results obtained through randomized controlled bioefficacy trials conducted by nutritionists, and through farmer-adoption models estimating impact at scale. Farmer and consumer surveys and monitoring systems provided the underlying information for estimating farmer adoption models and helped understand input/output markets, farmer and consumer preferences, and additional opportunities and challenges –all of which informed crop breeding and delivery activities, while building the knowledge base for catalyzing the scaling of biofortification.